Neutron Beam Characterization at the Athens Tandem Accelerator NCSR “Demokritos” - Vlastou, R.; Sigalas, D.; Kalamara, A.; Kokkoris, M.; Anastasiou, M.; Diakaki, M.; Axiotis, M.; Lagoyannis, A. (HNPS Advances in Nuclear Physics, 2019)
A new Ti-tritiated target of 373 GBq activity has been installed at the 5.5MV tandem T11/25 Accelerator of NCSR "Demokritos", to produce neutrons in the energy range ~15-21 MeV by means of the 3H(d,n)4He reaction. The flux variation of the neutron beam is monitored with a BF3 detector, while the absolute flux is obtained with respect to reference reactions, such as the 27Al(n,a) reference reaction. In absence of time-of-flight capabilities, the energy spectrum of the neutron beam has been investigated by means of Monte Carlo simulations as well as by the Multiple Foil Activation Analysis technique, using reactions with different energy thresholds. The experimental results have been compared with the simulated ones in order to validate the simulations